2019 IEEE International Electric Machines &Amp; Drives Conference (IEMDC) 2019
DOI: 10.1109/iemdc.2019.8785221
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of conventional and segmental rotor 12/10 switched reluctance motors

Abstract: Segmental rotor Switched Reluctance Machines (SRMs) have been demonstrated to produce more torque than toothed rotor SRMs because each coil is able to link more magnetic flux. This paper considers a six-phase segmental rotor SRM and compares it to a conventional SRM with the same lamination length and outer dimensions. Both fully-pitched (FP) and single-tooth wound (STW) motor configurations of the segmental rotor SRM are investigated. The FP winding machine produces higher torque than the single tooth winding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The proposed SRM with segmental rotor had over 40% higher torque than the CSRM regarding the same winding loss in the theoretical analyses study in [62]. In [56], the SRM with the segmental rotor produced much higher average torque compared to the CSRM. The two-stack SRM with segmental rotor introduced in [59] obtained 19% torque ripple reduction and 10% average torque increase.…”
Section: Summary and Comparison Of Segmental Structuresmentioning
confidence: 76%
See 1 more Smart Citation
“…The proposed SRM with segmental rotor had over 40% higher torque than the CSRM regarding the same winding loss in the theoretical analyses study in [62]. In [56], the SRM with the segmental rotor produced much higher average torque compared to the CSRM. The two-stack SRM with segmental rotor introduced in [59] obtained 19% torque ripple reduction and 10% average torque increase.…”
Section: Summary and Comparison Of Segmental Structuresmentioning
confidence: 76%
“…A comparison between the segmental SRM (segSRM) and the CSRM was performed in [56]. Their result showed that the segSRM produces about 10% higher rated torque throughout the entire speed range and creates less core loss and less copper loss compared to the CSRM.…”
Section: One-stack Structure Of the Segsrmmentioning
confidence: 99%
“…A segmented structure of the SRSM, called segmented SRSM (SSRSM) was proposed to solve this problem. The SSRSM had increased the SRSM's torque efficiency by approximately 50% compared to the conventional design of the same size and at the same time reduced the torque ripple [7], [48].…”
Section: Structure Topology Of Srsmsmentioning
confidence: 99%
“…The operation principle of SRMs is that the magnetic flux is always closed along the path of maximum magnetic permeability to generate magnetic torque, and the flux distribution is associated with the winding connection, the arrangements of poles polarity and the number of excitation phases. Generally, there are three winding connection patterns, such as short-pitched CSRM (SCSRM), 34,52,[65][66][67][68][69] fully-pitched CSRM (FCSRM), [70][71][72][73][74][75][76][77] and toroidal winding SRM (TSRM), [78][79][80][81] take threephase SRM as an example and three SRMs are shown in Figure 5.…”
Section: Winding Topologiesmentioning
confidence: 99%
“…However, the fully-pitched winding is suitable for segment rotor SRMs, for the mutual inductance is only exist in the adjacent two-phase windings, for example, the fully-pitched winding is used in four-phase SSRM in Chen et al 82 and six-phase-phase in Deng and Mecrow. 75 Comparison of four-phase segmented-type SRM (SSRM) with short-pitched winding and fullypitched winding is shown in Figure 7(c) and the comparison values are presented in Table 3. It can be found that SSRM with fully-pitched winding can produce higher torque than the CSSRM.…”
Section: Winding Topologiesmentioning
confidence: 99%